1999
DOI: 10.1016/s0014-2999(98)00881-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corticosteroid, contrast medium and ATP on focal microcirculatory disorders of the cochlea

Abstract: We evaluated the ability of various drugs to prevent the decrease in focal cochlear blood flow induced by photochemical reaction and investigated the mechanisms underlying this decrease. By means of a photochemical reaction, which produces reactive oxygen species, focal lesions measuring about 1 mm in diameter were induced in the lateral wall of the guinea pig cochlea. The protective effects of hydrocortisone, amidotrizoate and ATP on cochlear blood flow and cochlear vascular conductance changes were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…8 Intratympanic steroids are used in 1991 by Itoh in the treatment of Meniere's disease. 9 Its use in SSNHL documented by silverstein in 1996; 10-14 this is followed by many authors who described use of Intratympanic steroids for SNNHL. The mode of action, its efficacy and consistency of this therapy is not clear, but it is widely used.…”
Section: Discussion: Sudden Sensorineural Hearing Loss Is One Of the mentioning
confidence: 98%
See 1 more Smart Citation
“…8 Intratympanic steroids are used in 1991 by Itoh in the treatment of Meniere's disease. 9 Its use in SSNHL documented by silverstein in 1996; 10-14 this is followed by many authors who described use of Intratympanic steroids for SNNHL. The mode of action, its efficacy and consistency of this therapy is not clear, but it is widely used.…”
Section: Discussion: Sudden Sensorineural Hearing Loss Is One Of the mentioning
confidence: 98%
“…8 The main role of steroids is to protect the cochlea from inflammatory mediators released like TNA-a and NFK b. 9 Steroids increase the blood flow to the cochlea and regulate protein synthesis in cochlea. 10 Striae vascularis which is the principal site of injury; Steroids improve its function.…”
Section: Discussion: Sudden Sensorineural Hearing Loss Is One Of the mentioning
confidence: 99%
“…On the contrary, Hafezi-Moghadam et al [18] claimed that vessel dilatation and subsequent blood flow increase were caused by high dose DEX through activating endothelial nitric oxide synthase (eNOS) with subsequent production of nitric oxide(NO) in acute myocardial infarction. Nagura et al [19] proposed that intravenous hydrocortisone could prevent photochemically induced CoBF decrease with more prominent effect than vasodilators, such as amidotrizoate and ATP (adenosine triphosphate), due to its anti-oxidative effects. Lastly, Lamm and colleague [14] revealed no significant change of CoBF by intravenous high and low dose prednisolone in noise-damaged guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,8 The precise mechanism by which steroids may improve hearing remains unknown; both glucocorticoid and mineralocorticoid receptors may be found in the inner ear. 28 A few studies have shown that the main roles of steroids in the treatment of SHL are to protect the cochlea from the harmful effects of inflammatory mediators such as the tumor necrosis factor (TNF-a and NFK-b), which is elevated in infection and inflammation, 29 to increase cochlear blood flow 30 thereby avoiding cochlear ischemia, 31 to avoid noise-induced hearing loss, 32 and to regulate protein synthesis in the inner ear. 33 Studies have shown that the vascular stria, which regulates Na/K secretion for maintaining the endocochlear potential, is a site of injury in SHL.…”
Section: Discussionmentioning
confidence: 99%